ISLAMIC LAW PERSPECTIVE ON THE ROLE OF PAWNLOYERS IN THE DISTRIBUTION OF FUNDS TO MICRO-SMALL BUSINESS ENTERPRISES - Syaeful Bakhri; Aan Jaelani; Miyah Listiani (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
Difficult access to sources of capital is still a major problem in business development for Micro and Small Enterprises (UMK). This has attracted the attention of various parties, including the government. Different support and efforts of the government and the private sector in developing MSEs have been carried out, ranging from coaching to financing. One of the government's efforts is to establish a sharia pawnloyers as a non-bank financial institution that functions as a distributor of sharia-based funds. The purpose of this study was to determine the perspective of Islamic law on the procedures for distributing funds to MSEs in sharia pawnloyers. The research method used is descriptive qualitative, which is considered suitable to provide perspectives from various data sources. The results of the analysis explain that the procedure for distributing funds at Islamic pawnloyers is easy to do, and the process is fast so that it can ease the burden on customers. However, some obstacles are still encountered in the distribution process. According to the perspective of Islamic law, sharia pawnloyers are following sharia principles in channeling funds to MSEs.